2019
DOI: 10.1101/541656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The functional landscape of the human phosphoproteome

Abstract: Protein phosphorylation is a key post-translational modification regulating protein function in almost all cellular processes. While tens of thousands of phosphorylation sites have been identified in human cells to date, the extent and functional importance of the phosphoproteome remains largely unknown. Here, we have analyzed 6,801 publicly available phospho-enriched mass spectrometry proteomics experiments, creating a state-of-the-art phosphoproteome containing 119,809 human phosphosites. To prioritize funct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 86 publications
0
76
0
Order By: Relevance
“…Like PhosphoSitePlus (PSP) and PhosphOrtholog, the sequence window filters out phosphosites in structural protein domains such as I‐set, leaving a higher proportion of phosphosites in domains that are frequently of interest, including protein kinase and transcription factor domains (Appendix Fig S2A–D). As expected from expanding the stringency from PSP and PhosphOrtholog, the functional prediction score (preprint: Ochoa et al , ) was intermediate compared to all phosphosites identified in human muscle and high confidence mapped orthologs (Appendix Fig S2E). Mapping potential orthologs by sequence window resulted in the identification of 190 phosphosites regulated in all three models (114 up‐ and 76 down‐regulated phosphosites), representing 80 proteins (Table EV2).…”
Section: Resultsmentioning
confidence: 83%
“…Like PhosphoSitePlus (PSP) and PhosphOrtholog, the sequence window filters out phosphosites in structural protein domains such as I‐set, leaving a higher proportion of phosphosites in domains that are frequently of interest, including protein kinase and transcription factor domains (Appendix Fig S2A–D). As expected from expanding the stringency from PSP and PhosphOrtholog, the functional prediction score (preprint: Ochoa et al , ) was intermediate compared to all phosphosites identified in human muscle and high confidence mapped orthologs (Appendix Fig S2E). Mapping potential orthologs by sequence window resulted in the identification of 190 phosphosites regulated in all three models (114 up‐ and 76 down‐regulated phosphosites), representing 80 proteins (Table EV2).…”
Section: Resultsmentioning
confidence: 83%
“…But rather than the high throughput methods that first identified the PTMs, low throughput methods are required to pinpoint effects on individual enzymes. This has presented a serious bottleneck for phosphorylation studies, which will be eased by innovations like machine-based learning approaches that help to prioritise likely functional sites (43).…”
Section: Interplay Between Ptmsmentioning
confidence: 99%
“…A similar trend is starting to be observed in proteomics, where reuse of public datasets is becoming increasingly popular, with multiple applications 30,31 . Some examples where joint reanalysis of large public datasets has been performed involved the creation of comprehensive maps of the human proteome 32 and of human protein complexes 33 , or the characterisation of the functional human phosphoproteome 34 .…”
Section: Introductionmentioning
confidence: 99%